Control of Rice Blast Disease Using Antagonistic Yeasts - Kunyosying, D.; To-anun, C.; Cheewangkoon, R. (International Journal of Agricultural Technology, 2018)
Sixty three epiphytic yeasts isolated from various vegetable fruit surfaces and rice leaves were selected for antagonistic screening against rice blast disease caused by the fungus Pyricularia oryzae. In vitro screening was undertaken to assess the antagonistic potential of the yeasts. Preliminary testing showed that eight isolates inhibited growth by more than 50%. Then the five most antagonistic isolates: CMY047, CMY018, CMY045, CMY113 and CMY057, were selected to conduct further growth inhibition tests using the dual culture method. These isolates suppressed growth of the fungus by 62.86, 55.17, 54.28, 53.21 and 51.43%, respectively. Then the antagonistic yeasts were tested for their pathogen spore germination inhibition by the slide culture technique. Spore germination was observed under a microscope at 3, 6, 12 and 24h following test initiation. All antagonistic yeasts delayed but did not completely inhibit spore germination. Furthermore, antagonistic yeast isolates CMY045 and CMY018 significantly reduced appressorium formation and length of the germ tube when compared to the control treatment. In a greenhouse experiment, the yeast isolates CMY045 and CMY018 significantly reduced disease incidence to 15.20 and 17.06% respectively when compared with the control treatment (80.14%). Similar results were obtained in a field experiment.